Da capoeira escrava em Salvador a um método nacional de ensino: a luta regional de Mestre Bimba em questão - Marinho, Nilene Matos Trigueiro (2020)
The research is dedicated to understanding the relevance for capoeira, of the teaching methodology developed by Mestre Bimba, in his academy, in facing the negative social perception that related it to the activity of vagrants and rascals, at the end of the 19th century and early 20th century. Mestre Bimba developed a capoeira with connotations of gesture and body that brought it closer to the behaviors and body codes of western sports that gained notoriety in Brazil, from the 19th century onwards, whereas, it distanced itself from street practices, recognized by disorder and absence of rules capable of curbing the violence expressed in Brazilian cities like Salvador. The aforementioned changes are perceived, in the respective work, as part of the Brazilian civilizing effort, intensified in the cities as a result of historical events, such as: the abolition of slavery, in 1888; the creation of the Republic, in 1889; industrialization and urbanization in the 1920s; responsible for increasing the interdependence relationships between individuals and forming new figurations. Given the above, the guiding question was as follows: What changes in the figuration and interdependence processes allowed various behaviors associated with slave capoeira to be abandoned at Mestre Bimba's academy, in favor of a practice that required an education of emotions from its students, gestures and the body? It is a bibliographic-documentary research, whose sources used were newspapers that proved to be rich and capable of elucidating issues pertinent to the analysis; criminal proceedings of the 19th and 20th centuries; and literary sources that helped build the historical recovery of the issue. It is important to clarify that, the methodology assumed in the work called figurational sociology, is based on Elias (2011), when understanding the relevance in studying the long-term historical processes, from the influence of the civilizing effort to which the individuals are submitted , since childhood, to a greater or lesser degree, with greater or lesser success. Mestre Bimba was a subject with little education, who insisted on bringing the teaching model adopted in his academy closer to that developed in school education and sports, when he followed rites similar to these in his events called graduation, specialization, among others. In addition to being a way of taking his work to people with a higher level of education, he seemed to understand the mechanisms of society in progress in Brazil, gradually closer to technical-scientific principles, where academic knowledge became more valued , to the detriment of popular knowledge. Aware of the importance of his work, but less aware of the barriers that he would have to overcome until that moment, Mestre Bimba perceives himself as someone who made a great contribution to Brazilian culture, in seeking to overcome the stigmas that involved capoeira and even the stigmas related to the social insertion / projection of black and poor individuals. He was not the type who was satisfied with waiting for future recognition, not least because he had urgent needs, family, children and it was from capoeira that he took his livelihood. For this reason, he fought for it with full awareness of his own worth. And it was from the perspective of the “me” that the work sought to understand Bimba's feelings and his disappointment in relation to what he considered as abandonment of Bahian society. Recognition, and even success anywhere else in the world, would not make him overcome the rejection he had received from his land, Salvador. By dedicating himself fervently to the teaching of capoeira, he aimed to stand out among his closest circle of friends and in the city where he lived, but unfortunately he did not succeed.